In vivo near-infrared imaging for the tracking of systemically delivered mesenchymal stem cells: tropism for brain tumors and biodistribution - Kim SM (Dove Medical Press, 2015)
Seong Muk Kim,1 Chang Hyun Jeong,2 Ji Sun Woo,2 Chung Heon Ryu,1 Jeong-Hwa Lee,3 Sin-Soo Jeun1,21Postech-Catholic Biomedical Engineering Institute, College of Medicine, The Catholic University of Korea, Seoul, South Korea; 2Department of Neurosurgery, Seoul St Mary’s Hospital, The Catholic University of Korea, Seoul, South Korea; 3Department of Biochemistry, College of Medicine, The Catholic University of Korea, Seoul, KoreaAbstract: Mesenchymal stem cell (MSC)-based gene therapy is a promising tool for the treatment of various neurological diseases, including brain tumors. However, the tracking of in vivo stem cell migration, distribution, and survival need to be defined for their clinical application. The systemic routes of stem cell delivery must be determined because direct intracerebral injection as a cure for brain tumors is an invasive method. In this study, we show for the first time that near-infrared (NIR) imaging can reveal the distribution and tumor tropism of intravenously injected MSCs in an intracranial xenograft glioma model. MSCs were labeled with NIR fluorescent nanoparticles, and the effects of the NIR dye on cell proliferation and migratory capacity were evaluated in vitro. We investigated the tumor-targeting properties and tissue distribution of labeled MSCs introduced by intravenous injection and followed by in vivo imaging analysis, histological analysis, and real-time quantitative polymerase chain reaction. We observed no cytotoxicity or change in the overall growth rate and characteristics of labeled MSCs compared with control MSCs. NIR fluorescent imaging showed the organ distribution and targeted tumor tropism of systemically injected human MSCs. A significant number of MSCs accumulated specifically at the tumor site in the mouse brain. These results suggest that NIR-based cell tracking is a potentially useful imaging technique to visualize cell survival, migration, and distribution for the application of MSC-mediated therapies in the treatment of malignant gliomas.Keywords: mesenchymal stem cells, near-infrared nanoparticles, glioma, systemic delivery, in vivo imaging